Kesantunan Berbahasa dan Identitas dalam Media Sosial - Lusi Lian Piantari; Sherien Sabbah (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2025)
Online interaction has now become an inevitability. The rapid development of information technology has affected almost every aspect of life, including human interaction. Social media has become one of the most intensive venues for interaction. This research is based on the increasing intensity of conversations on social media, which has blurred the boundaries of politeness. Therefore, it is interesting to observe how participants strive to maintain this politeness. This study focuses on how linguistic politeness emerges on social media, specifically Twitter. One characteristic of social media conversations is the unlimited number of participants, as well as the diversity of their backgrounds. This often gives rise to conflict, especially when controversial topics are discussed. The research method employed is discourse analysis within a pragmatic approach to examine the politeness strategies used, particularly when conveying disagreement or dissatisfaction. This study describes the patterns of politeness strategies on Twitter and the identities performed by participants in interaction. The positive and negative politeness strategies are applied in social media interaction.Keywords: Identity, Politeness Strategies, Social Media, Twitter (X)